Pengaruh Biaya Produksi, Lama Usaha, Produktivitas Terhadap Pendapatan Petani Salak Pondoh Di Desa Pronojiwo Kecamatan Pronojiwo Kabupaten Lumajang - Aditya Purnomo; Moehammad Fathorrazi; Sebastiana Viphindrartin (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
This study aims to determine the effect of variable of costs production, years of farming, the productivity of the farmers of pondoh bark in Pronojiwo village Pronojiwo subdistrict Lumajang Regency. The analytical method used was Ordinary Least Square (OLS) which the income as the dependent variable and production costs, years of farming and productivity as independent variables. Based on the OLS analysis results, it showed that the variable cost of production and productivity had positive and significant effecton the farmers' income. While the years of farming had a negative effect and no significant effect on farmers' income. It was along with the growing era of information which can easily be obtained, so years of farming done does not guarantee the increasing the farmers' income.Keywords: Income, Cost of Production, Years of Farming, Productivity